4=-2x+3

Simple and best practice solution for 4=-2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4=-2x+3 equation:


4=-2x+3

We simplify the equation to the form, which is simple to understand
4=-2x+3

We move all terms containing x to the left and all other terms to the right.
+2x=+3-4

We simplify left and right side of the equation.
+2x=-1

We divide both sides of the equation by 02 to get x.
x=-0.5

See similar equations:

| 2x+40-4x=1-7x+4 | | 1205(2w-13)=3(2w-5) | | 2ab*3+3xb*2-5b*4+2b*2= | | csquared-5c=0 | | 5n+6n^4-7n+15n^4+13n=x | | (5x-8)(x^2+9x-10)= | | 3x^4+12x^3-36x^2=0 | | 1.4-0.2x=3.2 | | 0.07+0.4x=2 | | 5n-1=2n+8 | | 3b-9-86=11 | | -3p+2=2p+12 | | 3x^1+12x=0 | | 8lx-9l+8=32 | | 4m+7=9m-3 | | 2.4=4.2 | | 1008/48 | | 3(9-8x)+8(3x+4)=11 | | 5x-2y+20=0 | | 10-(4x-5)=6-5x | | 4w-16=12+3w | | 5w-2(w-18)=7w-15 | | (x+1)/(x-3)-3/5=4/(x-3) | | 2d^2+12d/d+6 | | 4x+5=3(x+15) | | x(3x-2)+x(4x-5)=(7x+4)(x-1) | | x+1/x-3-3/5=4/x-3 | | 3.7x-1.9=-9.3 | | 12x-8+3x-4=11x-2+3x | | 5b-20=10b+5 | | (4x^2+6x-2)+(6x^2-9x+5)= | | x^4-16x^3+60x^2=0 |

Equations solver categories